Evaluating outcomes of mother–infant pairs using dolutegravir for HIV treatment during pregnancy. (10th September 2018) - Grayhack, Clara; Sheth, Anandi; Kirby, Olivia; Davis, Jennifer; Sibliss, Kedesha; Nkwihoreze, Hervette; Aaron, Erika; Alleyne, Gregg; Laguerre, Roberta; Rana, Aadia; Badell, Martina; Momplaisir, Florence
Abstract : Objectives: Dolutegravir (DTG), a second-generation integrase inhibitor, is an effective treatment for HIV but its safety and efficacy are not well established in pregnancy. Here, we assess maternal and infant outcomes of mother–infant pairs using DTG-containing regimens during pregnancy. Methods: We performed a retrospective cohort analysis of pregnant women with HIV on DTG from two urban clinics in the United States, 2015–2018. Maternal outcomes included viral suppression (viral load of <20 copies/ml prior to delivery), development of resistance, and tolerability to DTG. Infant outcomes included preterm delivery (birth at <37 weeks), small for gestational age (SGA, weight <10th percentile), infant HIV status at birth, birth defect(s), and Appearance, Pulse, Grimace, Activity, Respiration (APGAR) scores. We performed a trend analysis to assess DTG use over time. Results: A total of 66 women used DTG during pregnancy and the proportion on DTG increased each year: in 2015, 8% (5/60) of women were on DTG, versus 22% (15/67) in 2016, 42% (30/71) in 2017, and 59% (16/27) in 2018 ( P < 0.05). Among women who delivered ( n = 57), 77.2% were undetectable at delivery. There were no drug resistance and no reported side effects during pregnancy. Infants had a mean APGAR score of 8 (SD 1.5) at 1 min and 9 (SD 0.8) at 5 min; 31.6% were born prematurely and 15.8% were SGA, and 2 infants had a birth defect. No cases of HIV transmission occurred. Conclusion: Our findings suggest that DTG can be an effective treatment during pregnancy. Infant outcomes (preterm deliveries and birth defects) need to be investigated in larger studies.